Language learning strategy research in System: Looking back and looking forward. (August 2019) - Zhang, Lawrence Jun; Thomas, Nathan; Qin, Tony Limin
Abstract: The herald of the seminal work on language learning strategies by Rubin (1975) and Stern (1975) has undoubtedly impacted how we view learning and teaching nowadays. Such impact was not so much felt in the 1970s, when this work just started. Scholarly embracing of such an approach was evidently witnessed in the very first article on reading strategies of successful and unsuccessful language learners by Hosenfeld (1977) published in System, with other scholars' work to follow thereafter. By 2019, the number of research articles on language learning strategies in the journal has risen to 118. We briefly examine the historical trajectory and analyse major trends and issues of this line of research in relation to the articles published in System. As a way of showing how language learning strategy research has contributed to the enterprise of language learning and teaching in its almost 45 year history and anticipate what lies ahead as possible areas for further investigation, we have selected 13 "representatives" (with one already being an Open Access article) from a list of 59 research articles published in System in the recent decade to help our readers to appreciate, critique, and further ponder over this apparently mature terrain in our field.